AB0278 The effect of rheumatoid factor titer on the response to TNF antagonists. (23rd January 2014) - Salgado, E.; Campos, J.; Moreira-Navarrete, V.; Mulero, J.; Navarro, F.; Perez-Pampin, E.; Carmona, L.; Gomez-Reino, J.J.
Abstract : Background: Different mechanisms have been proposed to explain the lack of response to TNF antagonists in Rheumatoid Arthritis (RA). These included the potential binding of Rheumatoid Factor (RF) to the Fc region of the drug, causing conformational changes or immune complex formation. (1, 2) Objectives: To examine whether rheumatoid factor (RF) is a predictor of response to TNF antagonists in rheumatoid arthritis (RA) Methods: All patients with RA treated with TNF antagonists for at least 6 months at three different centers were included in this longitudinal study. Response at 24 weeks was assessed as EULAR good/moderate categories pooled together, and change in DAS28-ESR from baseline (DDAS28). The predictive value of baseline titer of IgM RF was analyzed. Results: 374 patients were included; 271 (73%) had elevated IgM RF at baseline. At sixth month, 303 (81%) patients were responders. Baseline characteristics of patients and concomitant treatment of both groups are shown in table. There were no statistical differences in baseline IgM RF titer in responders and non-responders (Mann-Whitney, p>0, 05). Also, baseline IgM RF status (positive/negative) and EULAR response were not related (Chi-squared, p>0, 05). DDAS28-ESR did not correlate with IgM RF titer (rho -0, 02, p>0, 05) or RF status (t test, p>0, 05). A multivariate logistic regression model adjusted for glucocorticoids, methotrexate, and number of prior DMARDs, did not modify the association between RF titer and response. Conclusions: This large observational study in RA fails to demonstrate association of baseline IgM RF and response to TNF antagonists. References: Marotte H, Miossec P. Biomarkers for prediction of TNFα blockers response in rheumatoid arthritis. Joint Bone Spine 2010; 77(4):297-305. Bozsoky S, Franklin EC. The effects of chemical modifications of human gamma-globulins on their interaction with rheumatoid factors and antibodies. Arthritis Rheum 1966; 9(3):405-413. Disclosure of Interest: None Declared